2009
DOI: 10.1007/s12144-009-9062-1
|View full text |Cite
|
Sign up to set email alerts
|

Resilience in Families that have Experienced Heart-Related Trauma

Abstract: STATEMENT I, the undersigned, hereby declare that the work contained in this assignment is my own original work and that I have not previously in its entirety or in part submitted it at any university for a degree. ……………………….. ……………………… Signature Date ii ABSTRACTThe current study was aimed at expanding on and understanding the adaptation and adjustment mechanisms used by families in the wake of heart-related trauma, as a means of providing information that reveals and supports the family's own abilities, capab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 26 publications
(74 reference statements)
3
26
0
4
Order By: Relevance
“…These findings were confirmed in the best-subset regression analysis, thus validating the significant contribution of problem-solving communication patterns in predicting family adaptation. These findings also enjoy theoretical support (McCubbin & McCubbin, 1996;Walsh, 2002Walsh, , 2003 as well as empirical support (Greeff & Thiel, 2012;Greeff & Wentworth, 2009;Jonker & Greeff, 2009). …”
Section: Family Resilience In Caring For Dementiasupporting
confidence: 61%
See 3 more Smart Citations
“…These findings were confirmed in the best-subset regression analysis, thus validating the significant contribution of problem-solving communication patterns in predicting family adaptation. These findings also enjoy theoretical support (McCubbin & McCubbin, 1996;Walsh, 2002Walsh, , 2003 as well as empirical support (Greeff & Thiel, 2012;Greeff & Wentworth, 2009;Jonker & Greeff, 2009). …”
Section: Family Resilience In Caring For Dementiasupporting
confidence: 61%
“…The families in these studies relied on their internal strengths to help them through difficult situations. They were described as flexible and open to change, innovative and proactive when faced with new experiences, accepting, respectful, loving, and supportive towards one another, and willing to work together as a unit to overcome their problems (Greeff & Thiel, 2012;Greeff, Van Steenwegen & Ide, 2006;Greeff & Wentworth, 2009;Jonker & Greeff, 2009;McCubbin & McCubbin, 1988;Preece & Sandberg, 2005). The results also showed that families making use of passive appraisal as a coping strategy were better able to deal with the emotional hardships of caring for a chronically ill loved one.…”
Section: Department Of Psychology University Of Stellenbosch Stellementioning
confidence: 93%
See 2 more Smart Citations
“…The philosophical outlook towards life shaped their thoughts and prepared them to have positive orientation towards life. A further important resiliency quality relates to the individual characteristics of the family, which includes a positive outlook, and an understanding and acceptance of new circumstances This aspect refers to the way a family makes meaning of life's adversity (Chesla et al 2003;Greeff and Wentworth 2009;Patterson 2002;Walsh 2002 andMcCubbin 1996). Some psychologists claim trust is the hallmark of social adjustment (Gurtman 1992) and that without it neuroses prevail.…”
Section: Discussionmentioning
confidence: 99%